2007
DOI: 10.1037/0021-843x.116.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Failure of positive but not negative emotional valence to enhance memory in schizophrenia.

Abstract: Abnormalities in the integration of emotion and cognition have long been considered hallmark characteristics of schizophrenia. Study authors used a well-established emotional memory model from the neuroscience literature to assess the facilitative impact of emotional valence of information on long-term memory consolidation in schizophrenia. Participants with schizophrenia (n=33) indicated somewhat higher levels of emotional intensity in response to emotional images than did healthy (n=28) participants. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
84
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(94 citation statements)
references
References 78 publications
9
84
1
Order By: Relevance
“…Additional exploratory analysis revealed preliminary evidence that ketamine produces a valence-dependent pattern of impairments on longer-term recognition memory performance, with less severe impairments on negative stimuli in the context of intact emotional enhancement for negative information. Two previous studies examining the emotional subsequent memory effect in schizophrenia patients after longer consolidation intervals (< 24h) reported -in addition to generally impaired memory performance in the schizophrenia patients -greater rates of forgetting of both, positive and neutral stimuli than negative stimuli in a sample of long-hospitalized schizophrenia patients (Calev and Edelist, 1993), and a lack of emotional memory enhancement of positive, but intact enhancement of negative stimuli in a sample of stable-medicated schizophrenia patients (Herbener et al, 2007). However, given the preliminary nature of the emotion-specific behavioural effects of ketamine conclusions in this regard need to be drawn with caution.…”
Section: Potential Relevance For Schizophreniamentioning
confidence: 99%
See 2 more Smart Citations
“…Additional exploratory analysis revealed preliminary evidence that ketamine produces a valence-dependent pattern of impairments on longer-term recognition memory performance, with less severe impairments on negative stimuli in the context of intact emotional enhancement for negative information. Two previous studies examining the emotional subsequent memory effect in schizophrenia patients after longer consolidation intervals (< 24h) reported -in addition to generally impaired memory performance in the schizophrenia patients -greater rates of forgetting of both, positive and neutral stimuli than negative stimuli in a sample of long-hospitalized schizophrenia patients (Calev and Edelist, 1993), and a lack of emotional memory enhancement of positive, but intact enhancement of negative stimuli in a sample of stable-medicated schizophrenia patients (Herbener et al, 2007). However, given the preliminary nature of the emotion-specific behavioural effects of ketamine conclusions in this regard need to be drawn with caution.…”
Section: Potential Relevance For Schizophreniamentioning
confidence: 99%
“…A number of studies examined the ESM in schizophrenia patients to specifically probe the disintegration of emotion and cognition (Herbener, 2008). Most ESM studies observed normal emotional experience during encoding in schizophrenia patients (Lakis et al, 2011;Herbener et al, 2007;Hall et al, 2007), however, with regard to the specificity of impairments in the domain of the emotional subsequent memory effect findings remained inconsistent ranging from unspecific impairments (Lakis et al, 2011;Hall et al, 2007) to highly selective impairments for positive information only (Herbener et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…222,223 However, symptoms such as anhedonia and avolition also represent significant constraints on functional outcome in this illness. The presence of anhedonia is associated with poor community and social function 99,[224][225][226][227][228] and predicts poor longterm outcomes. 99,[229][230][231] It may turn out that some of the same mechanisms leading to cognitive deficits in schizophrenia also contribute to anhedonia and avolition, such as DLPFC-mediated disturbances in goal maintenance.…”
Section: Summary Suggestions For Future Research and Significancementioning
confidence: 99%
“…The presence of anhedonia is associated with poor community and social function 99,[224][225][226][227][228] and predicts poor longterm outcomes. 99,[229][230][231] It may turn out that some of the same mechanisms leading to cognitive deficits in schizophrenia also contribute to anhedonia and avolition, such as DLPFC-mediated disturbances in goal maintenance. 232,233 If so, then treatments aimed at improving cognitive function in schizophrenia may also improve anhedonia and avolition, though there is not yet clear evidence for this.…”
Section: Summary Suggestions For Future Research and Significancementioning
confidence: 99%